Sanksi Pidana terhadap Anak yang Melakukan Tindak Pidana Pencurian - Made Agus Rai Sanditya Wibawa; I Made Minggu Widyantara; Luh Putu Suryani (Warmadewa Press, 2022)
Legal protection for children who are faced with the law is one of the important issues that must be considered by all parties to avoid the negative impact felt by children if their rights are violated. The purpose of this study is to analyze the legal protection of children as perpetrators of the crime of theft, and to examine criminal sanctions against children who commit the crime of theft. The method used is normative legal research. This research approach is a conceptual and literature approach, with the primary legal sources coming from legislation and decisions, while the secondary legal sources come from legal journals and law books. Data collection is done by collecting data and summarizing. The results of the study show that legal protection for children as perpetrators of criminal cases is based on Law Number 11 of 2012 concerning the Juvenile Criminal Justice System, which is known as litigation, non-litigation through deversion, children who commit criminal cases are called with children in conflict with the law. Children in conflict with the law are children aged 12 (twelve) years, who are suspected of committing the crime of theft. This study shows that the sanctions are in accordance with the provisions of the juvenile criminal justice system, in which the child is punished for a maximum of seven years in prison or a fine of nine hundred thousand rupiahs